Comparison of ABTS and DPPH assays in estimating the total antioxidant capacity of Turmeric (Curcuma longa L.) rhizome - Bautista, Karina Angela D.
Antioxidants are compounds that target free radicals to delay or inhibit oxidation. These are commonly associated with phenolic compounds that are mostly present in plants. Turmeric Curcuma longa L., an herb from the ginger family of Zingiberaceae, contains curcumin which is responsible for not only the color of the plant but also its antioxidative properties. To maximize the potential of turmeric as a functional food, this study estimated the total antioxidant capacity TAC of turmeric rhizome using free radical scavenging spectrophotometric assays such as ABTS and DPPH assays. Methanolic extraction was done to prepare the turmeric extracts and a total phenolic content TPC of 84.019 2.790 mg GAE100g was determined using FolinCiocalteu Method. The ABTS and DPPH assays were established to have acceptable accuracy 80120 Recovery and precision RSD 5 however, only the DPPH assay showed acceptable linearity r2 0.95. Limit of Detection LOD and Limit of Quantitation LOQ were also established at 55.01M and 183.37M, respectively, for DPPH assay and at 28.38μM and 94.61M, respectively, for ABTS assay. The TAC of turmeric rhizome was estimated and expressed in terms of Scavenging Activity SA and in Trolox EquivalentsTE μmol TEg fresh wt. No significant correlation p 0.05 was found between TPC values and TAC determined using ABTS and DPPH assays. Likewise, there was no significant 0.05 correlation established between the TAC results from the two assays. In both assays, a significant p 0.05 correlation was established between the SA and the TE. Experimental procedures of antioxidant studies are highly sensitive and should be conducted in adherence with Good Laboratory Practices GLP. Validation should always be done before conducting an experimental procedure in order to ensure reliable results.